2023
DOI: 10.1021/acssuschemeng.2c05833
|View full text |Cite
|
Sign up to set email alerts
|

Refreshing DNA-Based Nanoprobes by Alcohol for Heavy Metal Detection: Toward Sustainable Sensing Nanomaterials

Abstract: Increasing the applications of disposable nanomaterials yet with potential environmental risk and the resulting nanowastes have become a problem of public concern worldwide. However, efficient recovery of useful materials from nanowastes is currently limited by their tiny size, high physicochemical activity, and unpredictable aggregation. We have developed a conceptually new strategy for recycling nanoprobes by alcoholic solvent “refreshing”. In specific, DNA-functionalized gold nanoparticles and nanorods are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Although colorimetric detection through magnesium pyrophosphate-induced turbidity change has gained popularity, the formation of the white precipitate may cause interference with the LAMP reaction . In the past few years, gold nanoparticles (AuNPs) with strong plasmon resonance and high extinction coefficient have gained popularity as a colorimetric indicator for recognition events, , which showcase the potential to substitute fluorescent dyes in LAMP assays. Indeed, it has been reported that the interaction of AuNPs with ssDNA primers and Bst DNA polymerase can boost the specificity of amplification in LAMP reactions .…”
mentioning
confidence: 99%
“…Although colorimetric detection through magnesium pyrophosphate-induced turbidity change has gained popularity, the formation of the white precipitate may cause interference with the LAMP reaction . In the past few years, gold nanoparticles (AuNPs) with strong plasmon resonance and high extinction coefficient have gained popularity as a colorimetric indicator for recognition events, , which showcase the potential to substitute fluorescent dyes in LAMP assays. Indeed, it has been reported that the interaction of AuNPs with ssDNA primers and Bst DNA polymerase can boost the specificity of amplification in LAMP reactions .…”
mentioning
confidence: 99%